2009
DOI: 10.1073/pnas.0905756106
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation exposure to ambient polycyclic aromatic hydrocarbons and lung cancer risk of Chinese population

Abstract: Taking into consideration the variation in exposure concentration, respiration rate, and susceptibility, the overall population attributable fraction (PAF) for lung cancer caused by inhalation exposure to PAHs was 1.6% (IR, Ϸ0.91-2.6%), corresponding to an excess annual lung cancer incidence rate of 0.65 ؋ 10 ؊5 . Although the spatial variability was high, the lung cancer risk in eastern China was higher than in western China, and populations in major cities had a higher risk of lung cancer than rural areas. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
232
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(246 citation statements)
references
References 34 publications
8
232
2
4
Order By: Relevance
“…In other words, areas of high population density correspond to areas of a potentially high health effects. Similar conclusion was drawn by Zhang et al (2009) who quantify the inhalation exposure to ambient polycyclic aromatic hydrocarbons and lung cancer risk among Chinese population and found that population of major cities had a higher risk of lung cancer than those residing the rural areas. It must be, however, remembered that in this work, the Polish-wide population exposure to B(a)P was calculated as the populationweighted exposure, i.e., the average exposure per hypothetical inhabitant across specific geographic region.…”
Section: Resultssupporting
confidence: 63%
“…In other words, areas of high population density correspond to areas of a potentially high health effects. Similar conclusion was drawn by Zhang et al (2009) who quantify the inhalation exposure to ambient polycyclic aromatic hydrocarbons and lung cancer risk among Chinese population and found that population of major cities had a higher risk of lung cancer than those residing the rural areas. It must be, however, remembered that in this work, the Polish-wide population exposure to B(a)P was calculated as the populationweighted exposure, i.e., the average exposure per hypothetical inhabitant across specific geographic region.…”
Section: Resultssupporting
confidence: 63%
“…In northern China, PAH exposure comes primarily from coal combustion. Shanxi Province produced 300 million tons of coal in 2003 and ranked first in PAH emission among all Chinese provinces (23). Coincident with PAH emission, the prevalence of NTDs in Shanxi Province was the highest in the country (24), with a prevalence rate of as high as 13.9 per 1,000 in some rural communities (13).…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of PAHs were extensively detected around this country (Bi et al, 2003;Guo et al, 2003;Feng et al, 2006a;Feng et al, 2006b;Li et al, 2006;Luo et al, 2010), inducing elevated lung cancer risk to Chinese population via inhalation exposure (Zhang et al, 2009). PAHs released in China could also be dispersed rapidly through air, and many recent studies have shown that the elevated PAH concentrations are monitored in surrounding countries and continents located downwind of China, including Korea, Japan, and North America, which can be attributed to the outflow of PAHs from China under certain meteorological conditions (Killin et al, 2004;Lee et al, 2006;Tamamura et al, 2007;Lang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%